Immunotherapy in Gastrointestinal Cancers. (3rd July 2017) - Procaccio, Letizia; Schirripa, Marta; Fassan, Matteo; Vecchione, Loredana; Bergamo, Francesca; Prete, Alessandra Anna; Intini, Rossana; Manai, Chiara; Dadduzio, Vincenzo; Boscolo, Alice; Zagonel, Vittorina; Lonardi, Sara
Abstract : Gastrointestinal cancers represent a major public health problem worldwide. Immunotherapeutic strategies are currently under investigation in this setting and preliminary results of ongoing trials adopting checkpoint inhibitors are striking. Indeed, although a poor immunogenicity for GI has been reported, a strong biological rationale supports the development of immunotherapy in this field. The clinical and translational research on immunotherapy for the treatment of GI cancers started firstly with the identification of immune-related mechanisms possibly relevant to GI tumours and secondly with the development of immunotherapy-based agents in clinical trials. In the present review a general overview is firstly provided followed by a focus on major findings on gastric, colorectal, and hepatocellular carcinomas. Finally, pathological and molecular perspectives are provided since many efforts are ongoing in order to identify possible predictive biomarkers and to improve patients' selection. Many issues are still unsolved in this field; however, we strongly believe that immunotherapy might positively affect the natural history of a subgroup of GI cancer patients improving outcome and the overall quality of life.